Expansion and phase correlation of a wavelength tunable gain-switched optical frequency comb - Anandarajah, Aleksandra; Lakshmijayasimha, Prajwal D.; Kaszubowska-Anandarajah, ﻿﻿Aleksandra; Martin, Eamonn P.; Landais, Pascal; Anandarajah, Prince M. (My University, 2019)
A novel scheme for the expansion and phase correlation of a wavelength tunable gain-switched optical frequency comb (OFC) is presented. This method entails firstly combining two gain-switched OFCs and expanding them using a phase modulator. Subsequently, the phase correlation between all the comb lines is induced through four-wave mixing (FWM) in a semiconductor optical amplifier (SOA). In this article, the generation of 42 highly correlated comb lines separated by 6.25 GHz, with an optical carrier to noise ratio (OCNR) of more than 50 dB, is experimentally demonstrated. In addition, the wavelength tunability of the scheme, over 30 nm within the C band, is shown. Finally, the degree of phase correlation betweencomb lines is verified through RF beat tone linewidth measurements. The results show a five orders of magnitude reduction in the beat tone linewidth, due to FWM in an SOA
Keywords: wavelength tunable gain-switched optical frequency; Optical frequency comb; Four-wave mixing; Semiconductor optical amplifier; wavelength tunable gain-switched optical frequency